Facies reconstruction and detrital zircon geochronology of the Ingleside/Casper Formation - Nair, Kajal, author; Egenhoff, Sven, advisor; Singleton, John, advisor; Rocca, Monique, committee member (Colorado State University. Libraries, 2018)
Mixed siliciclastic-carbonate deposits of the Ingleside/Casper Formation in northern Colorado and southeastern Wyoming developed along the flanks of the Ancestral Front Range during the Late Paleozoic. This study establishes a sedimentological model for the Ingleside/Casper Formation along with using detrital zircon data to identify siliciclastic sediment sources for Late Paleozoic deposits in two Ancestral Rocky Mountain basins along the Ancestral Front Range and Uncompahgre Highlands. The stratigraphic successions of the Ingleside/Casper Formation display a diverse suite of carbonate and siliciclastic lithofacies in close lateral and vertical association with each other. The six different siliciclastic facies and their subfacies identified in this study include: (1) cross-bedded sandstone (tabular cross-bedded sandstone and trough cross-bedded sandstone), (2) horizontally-bedded sandstone, (3) massive sandstone, (4) conglomeratic sandstone, (5) ripple-laminated sandstone (asymmetric current ripples, moderately-steeply climbing ripples, and gently climbing ripples), and (6) silt-rich siliciclastic mudstone. The three different carbonate facies and their subfacies identified in this study include: (1) carbonate mudstone-wackestone, (2) carbonate packstone (packstone with non-skeletal grains and packstone with bioclasts), and (3) carbonate grainstone (grainstone with non-skeletal grains and grainstone with bioclasts). Thinning and/or pinching out of carbonate facies accompanied with a gradual increase in siliciclastic sedimentation is observed laterally across the study area from north to south. Eight stratigraphic intervals are recognized from correlations across a north-south transect of 120 km and each interval displays a lithofacies assemblage dominated either by carbonates or siliciclastics. Both carbonate and siliciclastic successions display small-scale fining-upward trends, with coarsening-upwards being partially or wholly absent across the study area. One of the eight intervals (termed Interval 6) is of significant interest in this study because it displays a unique lithofacies assemblage, with it being the only interval where trough cross-beds of facies 1B occur. Overall, carbonate units vary in the extent to which they onlap onto siliciclastic strata throughout the succession: Intervals 1 to 4 record a successive advance of onlap towards the south, whereas intervals 5 to 8 record a retreat of onlap and a successive northwards migration of carbonate strata. The nine different lithofacies and their subfacies identified in this study represent an array of shallow-marine paleoenvironments that include foreshore, shoreface, offshore transition, and offshore, and terrestrial settings comprising coastal eolian dunes and fluvial systems. Stratigraphic distribution of facies suggests that deposition in a shallow-marine environment alternated between dominantly siliciclastic and dominantly carbonate, mainly as a result of fluctuations in the input of siliciclastic sediment and its effect on carbonate deposition. In a distal direction, both siliciclastic and carbonate facies graded into carbonate mudstone that is identified as the most distal setting across all stratigraphic successions studied here. The Ingleside/Casper succession is interpreted to consist of two superimposed scales of sea-level fluctuations with the small-scale cycles represented by deepening-upwards successions across the study area, and a superimposed large-scale sea level curve recorded in the varying onlap of carbonates. The superimposed curve shows an overall transgression in the lower part of the succession succeeded by a regression in the upper part. Independent of this type of sea-level curve, dry eolian dunes dominated the stratigraphic record during Interval 6 and reflect a sharp change in climate to more arid conditions that accompanied the exclusive formation of dunes during this time. The sedimentological study suggests that deposition of the Casper/Ingleside Formation was governed by the two orders of sea-level oscillations and also climate change, both operating on two separate scales. The general fall in sea level and increase in aridity in the upper Ingleside/Casper Formation is attributed to the onset of a major Gondwanan glaciation phase that culminated during the Pennsylvanian-Permian transition which is likely to be located at the very top of this unit. Based on exclusively sedimentological considerations, this study therefore suggests that the Ingleside Formation, which is typically assigned a Permian age, was most likely deposited during the Late Pennsylvanian. This interpretation is also based on the correlation of the Coloradoan Ingleside Formation to the Casper Formation in Wyoming that contains a known Late Pennsylvanian fussuline assemblage. This study also presents new detrital zircon U-Pb geochronology data from the type section of the Ingleside Formation at Owl Canyon, and the Molas and Hermosa Formations near Molas Lake to understand Late Paleozoic sediment provenance and dispersal patterns across Colorado. U-Pb ages on 120-150 zircons were determined from each sample using LA-ICPMS, and ages with excessive discordance (>20% discordant or <5% reverse discordant) were rejected. All samples contain between 5% and 10% concordant Paleozoic aged zircons ranging from 330-490 Ma. Other significant age distribution peaks identified range between 990-1200 Ma, 1340-1500 Ma, 1600-1800 Ma, and 2500-3500 Ma. The wide spread of zircon age populations record a mixed Laurentian derivation comprising local and distal sediment sources. Paleozoic-age zircons are interpreted to coincide with high magmatic flux during the Taconic and Acadian orogenies in the Appalachian orogen. The diverse components in the U-Pb age data suggest that a widespread sand-dispersal system that transported local and distant sediment sources along the Ancestral Rockies was operational during the Late Paleozoic. Areas of eolian recycling observed in the Ingleside and Molas Formations points towards eolian systems playing an important role in transportation of distally-sourced zircons during Late Paleozoic time. Additionally, the U-Pb detrital zircon data indicate that a shift from non-marine to marine deposition across the Fountain-Ingleside transition was accompanied by a decrease in locally-sourced detrital zircons, most likely marking the cessation of Ancestral Front Range uplift. Conversely, the shift from non-marine to marine deposition across the Molas-Hermosa contact was accompanied by an increase in locally-sourced detrital zircons, most likely marking the initiation of the Uncompahgre uplift.